Topical and Conventional Systemic Treatments in Atopic Dermatitis: Have They Gone Out of Fashion? - Calabrese, Giulia; Licata, Gaetano; Gambardella, Alessio; De Rosa, Alina; Alfano, Roberto; Argenziano, Giuseppe (Dermatology Practical & Conceptual, 2022)
Atopic dermatitis is a Th2 disease, due to relapse of IL-4 and IL-13 by Th2 cells. Despite the approval by FDA of dupilumab, the first monoclonal antibody for the severe forms, traditional drugs remain a milestone for the treatment of this dermatosis. Dermatologists need a good knowledge of all therapies for an integrated and personalized management of patients.